Light-emitting device and display device
By adopting a double-layer film structure and specific material design in quantum dot light emitting devices, the problem of inconsistent carrier transmission is solved, the luminous efficiency and life are improved, and the efficient injection balance of holes and electrons is achieved.
Patent Information
- Application Number
- CN202310750473.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-21
- Publication Date
- 2024-12-24
AI Technical Summary
Quantum dot light emitting devices have challenges in optimizing luminescence efficiency and lifetime, mainly due to the differences in nanomaterials, the carrier transmission situation is inconsistent, making it difficult to simultaneously improve the efficiency and lifetime of the device.
The luminescent layer adopts a double-layer film structure, combining the specific material and thickness design of the hole transport layer and the electron transport layer, ensures efficient injection balance of holes and electrons, including using mobility between 2.01×10-3cm2/Vs to 10× The hole transport layer of 10-3cm2/Vs and the electron transport layer of 0.2×10-3cm2/Vs to 0.5×10-3cm2/Vs, the fluorescence quantum yield of quantum dots is greater than or equal to 70%, and the quantum dots of core-shell structures Material.
The efficiency and life of the light emitting device are significantly improved, and by optimizing the carrier injection and recombination efficiency, the aging speed of the device and the difficulty of film formation of the light emitting layer are reduced.
Smart Images

Figure CN119183305A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of display, and in particular to a light-emitting device and a display apparatus. Background Art
[0002] Light-emitting devices emit light by releasing energy through the recombination of electrons and holes, and are widely used in the field of lighting. In recent years, quantum dots (QDs) have attracted widespread attention from industry, academia, and research circles due to their advantages of high fluorescence quantum yield, good monochromaticity, continuously adjustable emission spectrum with size, and strong photochemical and thermal stability. Quantum dot light emitting diodes (QLEDs) constructed with quantum dots as the light-emitting layer have become one of the most active scientific research topics due to their many advantages such as low cost, high brightness, wide color gamut, and excellent solution processability, and have shown great competitive potential in the next generation of flat panel display and solid-state lighting applications.
[0003] Although QLED display technology is inherited and developed from OLED (Organic Light-Emitting Diode), the performance of the device can be improved by applying the existing theories in OLED to QLED. However, since quantum dots are nanomaterials, when paired with other functional layers, there are huge differences in the type of material, its own structural design and film quality, the film interface injection barrier between the quantum dot material and other functional layers, and the aging and attenuation of the material itself. As a result, when different quantum dots are used in the actual processing process, completely different carrier transmission conditions will appear in the device, which aggravates the difficulty of optimizing QLED devices, making it difficult to improve the luminous efficiency and life of QLED devices at the same time, greatly limiting its development. Therefore, for quantum dot materials with large differences, it is urgent to develop more targeted high-performance light-emitting devices. Summary of the invention
[0004] In view of this, the present application provides a light-emitting device and a display device, aiming to simultaneously improve the light-emitting efficiency and service life of the light-emitting device.
[0005] The embodiment of the present application is implemented as follows:
[0006] In a first aspect, the present application provides a light-emitting device, the light-emitting device comprising an anode, a hole transport layer, a light-emitting layer, and a cathode stacked in sequence, wherein the material of the light-emitting layer comprises quantum dots, and the thickness of the light-emitting layer is 1.6 to 2.3 times the average particle size of the quantum dots;
[0007] The mobility of the hole transport layer material is greater than 2.01×10 -3 cm 2 / Vs, less than 10×10- 3 cm 2 / Vs.
[0008] Optionally, in some embodiments of the present application, the energy level difference between the hole transport layer and the light emitting layer is 0.1 to 1.6 eV; and / or,
[0009] The mobility of the material of the hole transport layer is 2.5×10 -3 ~5×10 -3 cm 2 / Vs.
[0010] Optionally, in some embodiments of the present application, the HOMO energy level of the material of the hole transport layer is -5 eV to -6 eV.
[0011] Optionally, in some embodiments of the present application, the material of the hole transport layer includes any one of TFB, V-TPAVCBP:10% OPPI.
[0012] Optionally, in some embodiments of the present application, the fluorescence quantum yield of the quantum dots is greater than or equal to 70%.
[0013] Optionally, in some embodiments of the present application, the average particle size of the quantum dots is greater than 8 and less than 11 nm; and / or,
[0014] The quantum dot is a core-shell structure quantum dot, and the quantum dot has a first shell layer and a second shell layer from the inside to the outside, the material of the first shell layer is ZnSe, and the material of the second shell layer is CdZnS.
[0015] Optionally, in some embodiments of the present application, the ratio of the thickness of the first shell layer to the radius of the core of the quantum dot is 0.5 to 2:1; and / or,
[0016] The ratio of the thickness of the second shell layer to the radius of the core of the quantum dot is 0.4 to 2:1.
[0017] Optionally, in some embodiments of the present application, the light-emitting device further comprises an electron transport layer disposed between the cathode and the light-emitting layer;
[0018] The mobility of the material of the electron transport layer is 0.2×10 -3 ~0.5×10 -3 cm 2 / Vs; and / or,
[0019] The average particle size of the material of the electron transport layer is 2 to 12 nm.
[0020] Optionally, in some embodiments of the present application, the light-emitting device also includes an electron transport layer arranged between the cathode and the light-emitting layer, and the material of the electron transport layer includes one or more of metal oxides and doped metal oxides; the metal oxide includes one or more of ZnO, TiO2, SnO2, ZrO, Al2O3, WO3, HfO3, Ta2O3, ZrSiO4, BaTiO3, and BaZrO3; the metal oxide in the doped metal oxide includes multiple of ZnO, TiO2, SnO2, ZrO, Al2O3, WO3, HfO3, Ta2O3, ZrSiO4, BaTiO3, and BaZrO3, and the doping elements include one or more of Al, Mg, Li, In, Ga, Cd, Cs, and Cu.
[0021] Optionally, in some embodiments of the present application, the core material of the quantum dot is selected from at least one of a II-VI group compound, an IV-VI group compound, a III-V group compound and an I-III-VI group compound; the II-VI group compound is selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS , CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe; the IV-VI group compound is selected from SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, P At least one of SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, and SnPbSTe; the III-V group compound is selected from GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InN At least one of P, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb; the I-III-VI group compound is selected from at least one of CuInS2, CuInSe2 and AgInS2; and / or,
[0022] The anode and the cathode are independently selected from a doped metal oxide particle electrode, a composite electrode of metal and metal oxide, a graphene electrode, a carbon nanotube electrode, a metal electrode or an alloy electrode; the material of the doped metal oxide particle electrode is selected from one or more of indium-doped tin oxide, fluorine-doped tin oxide, antimony-doped tin oxide, aluminum-doped zinc oxide, gallium-doped zinc oxide, indium-doped zinc oxide, magnesium-doped zinc oxide and aluminum-doped magnesium oxide; the composite electrode of metal and metal oxide is selected from AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS, ZnS / Al / ZnS; the material of the metal electrode is selected from one or more of Ag, Al, Cu, Mo, Au, Pt, Si, Ca, Mg and Ba; and / or,
[0023] The light emitting device further comprises a hole injection layer disposed between the anode and the hole transport layer, wherein the material of the hole injection layer comprises poly(ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS), poly[(9,9'-dioctylfluorenyl-2,7-diyl)-CO-(4,4'-(N-(p-butylphenyl))diphenylamine)], polyarylamine, poly(N-vinylcarbazole), polyaniline, polypyrrole, N,N,N',N'-tetrakis(4-methoxyphenyl)-benzidine, 4-bis[N-(1-naphthyl)-N- One or more of] phenyl-amino] biphenyl, 4,4',4"-tri[phenyl(m-tolyl)amino]triphenylamine, 4,4',4"-tri(carbazole-9-yl)triphenylamine, 1,1-bis[(di-4-tolylamino)phenylcyclohexane, 4,4',4"-tri(diphenylamino)triphenylamine doped with tetrafluoro-tetracyano-quinodimethane, p-doped phthalocyanine, F4-TCNQ doped N,N'-diphenyl-N,N'-di(1-naphthyl)-1,1'-biphenyl-4,4"-diamine, hexaazatriphenylene-capronitrile.
[0024] Optionally, in some embodiments of the present application, the thickness of the anode is 20 to 200 nm; and / or,
[0025] The thickness of the cathode is 40 to 190 nm; and / or,
[0026] The thickness of the hole transport layer is 30 to 180 nm; and / or,
[0027] The thickness of the electron transport layer is 20 to 180 nm; and / or,
[0028] The hole injection layer has a thickness of 20 to 200 nm.
[0029] In a second aspect, the present application further proposes a display device, which includes the light-emitting device described above.
[0030] The technical solution provided in this application is for the case where the light-emitting layer is a double-layer film, and the hole mobility of the matching material is greater than 2.01×10 -3 cm 2 / Vs, less than 10×10 -3 cm 2 / Vs hole transport layer helps to enhance hole injection, overcome the injection difficulty caused by the double-layer film, improve the effective injection and efficient recombination of carriers in the device, improve the injection balance of holes and electrons, and thus improve the efficiency and life of the device. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.
[0032] Figure 1 is a schematic structural diagram of a light-emitting device proposed in one embodiment of the present application;
[0033] Reference numerals:
[0034] 100 - light-emitting device; 10 - anode; 20 - light-emitting layer; 30 - cathode; 40 - electron transport layer; 50 - hole transport layer; 60 - hole injection layer; 201 - quantum dots. DETAILED DESCRIPTION
[0035] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without making creative work belong to the scope of protection of the present application. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present application, and are not used to limit the present application.
[0036] In this application, unless otherwise specified, the directional words used, such as "upper" and "lower", refer specifically to the directions of the drawings in the accompanying drawings. In addition, in the description of the specification of this application, the term "including" means "including but not limited to".
[0037] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0038] In this application, "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural.
[0039] In the present application, "at least one" means one or more, and "plurality" means two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0040] In actual processing, when the film-forming effect of the quantum dots 201 used is poor, it is often necessary to improve the film-forming quality by forming a double-layer film. Figure 1 As shown, the double-layer film refers to a film formed by two layers of quantum dots 201 in the thickness direction. Generally speaking, the thickness of the double-layer film is 1.6 to 2.3 times the average particle size of the quantum dots 201 forming the film. For example, when the average particle size of the quantum dots 201 used is 10 nm and the thickness of the film formed is 16 to 23 nm, the film is roughly a double-layer film.
[0041] In some application scenarios where a double-layer film needs to be formed, a ligand is connected to the surface of the quantum dot 201, and the ligand includes a strong coordination ligand. In some embodiments, the raw material of the ligand includes at least one of substituted or unsubstituted C10-C24 chain organic carboxylic acid, substituted or unsubstituted C10-C24 chain organic amine, substituted or unsubstituted C1-C24 chain thiol, substituted or unsubstituted C10-C24 chain organic phosphine, substituted or unsubstituted C10-C24 chain organic phosphine oxide, and halide. Among them, "substituted or unsubstituted" means that the defined group can be substituted or unsubstituted. When the defined group is substituted, it should be understood that the defined group can be substituted by one or more substituents; the substituent is selected from at least one of C1-C8 alkyl, C1-C8 alkoxy and halogen; optionally, the substituent is selected from at least one of C1-C5 alkyl, C1-C5 alkoxy and halogen; or the substituent is selected from at least one of C1-C3 alkyl, C1-C3 alkoxy and halogen. The halogen refers to -F, -Cl, -Br or -I. Specifically, the organic carboxylic acid includes one or more of decacarboxylic acid (CAS: 334-48-5), undecylenic acid (CAS: 112-38-9), tetradecanoic acid (CAS: 544-63-8), oleic acid (CAS: 112-80-1) and stearic acid (CAS: 57-11-4); the organic amine includes one or more of oleylamine (CAS: 112-90-3) and octadecylamine (CAS: 124-30-1); the organic (oxygen) phosphine includes tris(CAS: 112-90-3) and octadecylamine (CAS: 124-30-1); One or more of octylphosphine (CAS: 4731-53-7) and trioctylphosphine oxide (CAS: 78-50-2); the thiol includes one or more of n-octylmercaptan (CAS: 111-88-6), dodecanethiol (CAS: 112-55-0) and octadecanethiol (CAS: 2885-00-9); the halide is selected from one or more of hydrofluoric acid, hydrochloric acid, hydroiodic acid, hydrobromic acid, metal fluoride, metal chloride, metal iodide and metal bromide.
[0042] The mass of the ligand accounts for 15% to 20% of the total mass of the quantum dots 201 and the ligand, for example, it can be 15%, 16%, 17%, 18%, 19%, 20% and values between any two of the above values. Within this range, it helps to improve the dispersibility of the quantum dots 201 and enhance its film-forming effect.
[0043] The strong coordination ligand refers to a ligand that can form a strong coordination bond with the surface cation of the quantum dot 201 and is not easy to fall off during the processing. The raw materials of the strong coordination ligand include one or more of substituted or unsubstituted C1-C24 chain thiols and halides. When the mass of the strong coordination ligand accounts for more than 8% and less than 15% of the total mass of the quantum dot 201 and the ligand, the quantum dot 201 needs to be prepared into a double-layer film to have a better film quality.
[0044] It can be understood that the content of the ligand and the strong coordinating ligand can be obtained by nuclear magnetic resonance and thermal gravimetric test detection, and the number of strong coordinating ligands on the surface of quantum dot 201 can be introduced during the synthesis process or introduced by ligand exchange. First, nuclear magnetic resonance can measure the content of specific ligands on the surface of quantum dot 201. Secondly, thermal gravimetric test can determine the total content of ligands on the surface of quantum dot 201. Finally, the difference between the ligands of the two is the content of other ligands. The specific test method for determining the content of specific ligands on the surface of quantum dot 201 by nuclear magnetic resonance is as follows: dissolve quantum dot 201 in a deuterated reagent, and add a specific amount of internal standard as a reference, and calculate the ratio of the chemical shift integrated area of the ligand of quantum dot 201 to the chemical shift integrated area of the internal standard, so as to quantify the ligand content to be measured. The thermal gravimetric test detection method is as follows: heat the quantum dot 201 material until its mass no longer changes, record the weight loss W1 of the material when it starts to lose weight to the shedding temperature of the strong coordinating ligand, and record the weight loss W2 of the material when it starts to lose weight to the time when its mass no longer changes, then W2 is the content of the ligand, and W2-W1 is the content of the strong coordinating ligand.
[0045] NMR and thermal gravimetric methods can also be used simultaneously, for example, to determine the content of specific quantum dot 201 surface ligands oleic acid (weak ligand) and thiol (thiol as a strong coordinating ligand). The specific test method is as follows: First, dissolve quantum dot 201 in deuterated toluene, use ferrocene as an internal standard (the amount added is rated, the chemical shift is 3.8-4.0ppm), and measure the chemical shift of quantum dot 201 ligand at 5.4-5.8ppm. Finally, divide the integral area of the chemical shift of the ligand at 5.4-5.8ppm by the integral area of the chemical shift of the internal standard at 3.8-4.0ppm to obtain the content of oleic acid ligand. Second, for example, measure the thermal gravimetric loss of quantum dot 201 at 20-600℃, and record the weight loss at 100℃-500℃, which is the total content of ligands on the surface of quantum dot 201. Finally, subtract the oleic acid ligand content from the total ligand content to obtain the thiol ligand content.
[0046] In some other embodiments, when the anions on the surface of the quantum dot 201 include sulfur atoms, for example, when the quantum dot 201 is CdS or CdSe / ZnSe / CdZnS, and the ligand is a thiol ligand, then when preparing the quantum dot 201, the thiol compound can be added as an anion source, and the S atoms on the ligand can be directly coordinated and connected with the cations on the surface of the quantum dot 201, or directly act as S atoms on the shell surface of the quantum dot 201 and be directly embedded in the shell, which helps to further improve the coordination effect of the ligand and reduce the probability of shedding.
[0047] However, the more layers of quantum dots 201 there are, the higher the barrier for carriers to tunnel through the quantum dots 201, which will limit the transmission of carriers and reduce the injection of carriers. In some embodiments, the present application provides a light-emitting device 100, which can be a quantum dot light-emitting diode (QLED), etc. Figure 1 The light-emitting device 100 includes a stacked anode 10, a hole transport layer 50, a light-emitting layer 20, an electron transport layer 40, and a cathode 30, wherein the material of the light-emitting layer 20 includes quantum dots 201, and the thickness of the light-emitting layer 20 is 1.6 to 2.3 times the average particle size of the quantum dots 201; wherein the mobility of the material of the hole transport layer 50 is greater than 2.01×10 -3 cm 2 / Vs, less than 10×10 -3 cm 2 / Vs.
[0048] The technical solution provided in this application is for the case where the light-emitting layer 20 is a double-layer film, and the hole mobility of the matching material is greater than 2.01×10 -3 cm 2 / Vs, less than 10×10 -3 cm 2 The hole transport layer 50 with a relative humidity of 400 W / Vs helps to enhance hole injection, overcome the injection difficulty caused by the double-layer film, improve the effective injection and efficient recombination of carriers in the device, and improve the injection balance of holes and electrons, thereby improving the efficiency and life of the device.
[0049] The mobility of the material of the hole transport layer 50 is greater than 2.01×10 -3 cm 2 / Vs, less than 10×10 - 3 cm 2 / Vs, for example, the hole mobility of the material used can be 2.02×10 -3 cm 2 / Vs, 2.03×10 -3 cm 2 / Vs, 2.1×10-3 cm 2 / Vs,3×10 -3 cm 2 / Vs,4×10 -3 cm 2 / Vs,5×10 -3 cm 2 / Vs,6×10 -3 cm 2 / Vs、7×10 -3 cm 2 / Vs,8×10 -3 cm 2 / Vs、9×10 -3 cm 2 / Vs,9.5×10 -3 cm 2 / Vs、9.8×10 -3 cm 2 / Vs,9.9×10 -3 cm 2 / Vs,9.99×10 -3 cm 2 / Vs and values between any two of the above values. Within this range, it is helpful to increase hole injection to a certain extent, improve the injection balance of holes and electrons in the device, thereby avoiding the light-emitting layer 20 being charged and inducing Auger recombination, which in turn affects the life and efficiency of the device.
[0050] Furthermore, in some embodiments, the mobility of the material of the hole transport layer 50 is 2.5×10 -3 ~5×10 -3 cm 2 / Vs, which helps to further improve the carrier balance.
[0051] In some embodiments, the absolute value of the energy level difference between the hole transport layer 50 and the light emitting layer 20 is 0.1 to 1.6 eV, for example, 0.1 eV, 0.3 eV, 0.5 eV, 0.7 eV, 0.9 eV, 1.0 eV, 1.1 eV, 1.3 eV, 1.5 eV, 1.6 eV, and values between any two of the above values. Within this energy level difference range, the hole injection barrier can be reduced, which helps to further enhance hole injection.
[0052] In some embodiments, the HOMO energy level of the material of the hole transport layer 50 is -5eV to -6eV; for example, -5eV, -5.2eV, -5.3eV, -5.4eV, -5.5eV, -5.6eV, -5.7eV, -5.8eV, -5.9eV, -6eV and values between any two of the above values.
[0053] Specifically, in some embodiments, the material of the hole transport layer 50 includes any one of TFB, V-TPAVCBP: 10% OPPI.
[0054] The Chinese name of TFB is poly[(9,9'-dioctylfluorenyl-2,7-diyl)-CO-(4,4'-(N-(p-butylphenyl))diphenylamine)]; CAS number: 223569-31-1; HOMO energy level is -5.3 eV; hole mobility is 3×10 -3 cm 2 / Vs.
[0055] V-TPAVCBP: 10% OPPI is derived from the literature "Chemically Doped Hole Transporting Materials with Low Cross-linking Temperature and High Mobility for Solution-Processed Green / Red PHOLEDs"; HOMO level is -5.37 eV; hole mobility is 4.9×10 -3 cm 2 / Vs.
[0056] In some embodiments, the average particle size of the quantum dots 201 is greater than 8 and less than 11 nm, for example, it can be 8.1 nm, 9 nm, 10 nm, 10.9 nm, and a value between any two of the above values, so that it is more conducive to the quantum dots 201 to form a double-layer film. Correspondingly, the thickness of the light-emitting layer 20 is 13 to 27 nm, for example, it can be 13 nm, 14 nm, 15 nm, 16 nm, 17 nm, 18 nm, 20 nm, 22 nm, 23 nm, 24 nm, 25 nm, 26 nm, 27 nm, and a value between any two of the above values.
[0057] Further, in some embodiments, the fluorescence quantum yield (QY) of the quantum dot 201 is greater than or equal to 70%, for example, it can be 70%, 75%, 80%, 85%, 90%, 92%, etc. Quantum dots 201 with higher QY usually have fewer defects, can reduce the probability of non-radiative recombination, and improve carrier recombination.
[0058] In some embodiments, the shape of the quantum dot 201 includes but is not limited to sphere, cube, tetrahedron, column, tetrapod, octapod, flake, etc.
[0059] In some embodiments, the quantum dot 201 is a quantum dot 201 of a core-shell structure, having a first shell and a second shell from the inside to the outside. The material of the first shell is ZnSe, and the shallow valence band helps to improve hole injection, but its own band gap is relatively moderate, and its ability to bind excitons is relatively weak; the material of the second shell is CdZnS, which not only has a relatively wide band gap, but also has a relatively moderate position of the valence band, which can ensure that the excitons are bound, and improve the hole injection into the luminescent core, thereby improving the carrier recombination efficiency. The two shells work together to effectively reduce the hole injection barrier, which helps to efficiently inject holes into the core of the quantum dot 201.
[0060] In some embodiments, the ratio of the thickness of the first shell layer to the radius of the core of the quantum dot 201 is 0.5 to 2:1; for example, the ratio can be 0.5:1, 0.6:1, 0.8:1, 1:1, 1.1:1, 1.2:1, 1.3:1, 1.5:1, etc.; this helps to effectively control the binding ability of excitons, which is not only beneficial to reduce the tunneling barrier during carrier injection and promote carrier injection, but also helps to effectively recombine the carriers injected into the core of the quantum dot 201.
[0061] In some embodiments, the ratio of the thickness of the second shell layer to the radius of the core of the quantum dot 201 is 0.4 to 2:1; for example, the ratio can be 0.4:1, 0.6:1, 0.8:1, 1:1, 1.2:1, 1.3:1, 1.5:1, 1.7:1, 1.8:1, 2:1, etc.; this helps to effectively control the binding ability of excitons and isolate the excitons from the outside world, thereby reducing the probability of excitons being captured by the outside world, while reducing the tunneling barrier during carrier injection and promoting carrier injection.
[0062] In some embodiments, the core material of the quantum dot 201 can be selected from but not limited to at least one of a II-VI compound, an IV-VI compound, a III-V compound, and an I-III-VI compound; as an example, the II-VI compound is selected from but not limited to CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgST e, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe; the IV-VI group compound is selected from but not limited to SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, At least one of SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, SnPbSTe; the III-V group compound is selected from but not limited to GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, A At least one of lPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb; the I-III-VI group compound is selected from at least one of CuInS2, CuInSe2 and AgInS2.
[0063] As an example, the core-shell structured quantum dots 201 may be selected from but not limited to at least one of CdZnSe / ZnSe / CdZnS, CdSe / ZnSe / CdZnS, InP / ZnSe / CdZnS, CdSeS / ZnSe / CdZnS, ZnSe / ZnSe / CdZnS, and ZnSeTe / ZnSe / CdZnS.
[0064] It should be noted that, for the core material of the core-shell structure quantum dot 201 or the shell material of the core-shell structure quantum dot 201, the chemical formula provided only indicates the element composition, but does not indicate the content of each element. For example, CdZnS only indicates that it is composed of three elements: Cd, Zn and S. If the content of each element is indicated, it corresponds to Cd x Zn 1-x S, 0 <x<1。
[0065] In some embodiments, the mobility of the material of the electron transport layer 40 is 0.2×10 -3 ~0.5×10 -3 cm 2 / Vs, for example, 0.2×10 -3 cm 2 / Vs, 0.21×10 -3 cm 2 / Vs, 0.25×10 -3 cm 2 / Vs, 0.28×10 -3 cm 2 / Vs, 0.3×10 -3 cm 2 / Vs, 0.35×10 -3 cm 2 / Vs, 0.4×10 -3 cm 2 / Vs, 0.45×10 -3 cm 2 / Vs, 0.5×10 -3 cm 2 / Vs and values between any two of the above values. Within this range, electron injection can be precisely controlled to improve the injection balance of holes and electrons in the device, thereby preventing the light-emitting layer 20 from being charged and inducing Auger recombination, which in turn affects the life and efficiency of the device.
[0066] In some embodiments, the average particle size of the material of the electron transport layer 40 is 2 to 12 nm, for example, 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 8 nm, 10 nm, 11 nm, 12 nm, and values between any two of the above values. The electron transport material with such a particle size is easy to be made into a film with uniform film thickness and dense film during film formation, which helps to improve the film quality.
[0067] In some embodiments, the material of the electron transport layer 40 includes, but is not limited to, one or more of metal oxides and doped metal oxides. As an example, the metal oxide includes, but is not limited to, one or more of ZnO, TiO2, SnO2, ZrO, Al2O3, WO3, HfO3, Ta2O3, ZrSiO4, BaTiO3, and BaZrO3; the metal oxide in the doped metal oxide includes, but is not limited to, multiple of ZnO, TiO2, SnO2, ZrO, Al2O3, WO3, HfO3, Ta2O3, ZrSiO4, BaTiO3, and BaZrO3, and the doping element includes, but is not limited to, one or more of Al, Mg, Li, In, Ga, Cd, Cs, and Cu.
[0068] In addition, in some embodiments, the surface of the electron transport material may be connected with a ligand, and the ligand includes one or more of an acid ligand, an amine ligand, and a thiol ligand. Specifically, the raw materials of the ligand include but are not limited to one or more of oleic acid, oleylamine, dodecanoic acid, tetradecanoic acid, hexadecanoic acid, and octadecanoic acid.
[0069] The metal oxide MO or the doped metal oxide MAO can be obtained by mixing the cation source, the alkali source and the solvent, wherein M is a metal element and A is a doping element. Specifically, when the material to be prepared is a metal oxide, the cation source is a metal salt that can provide the M metal element, such as zinc acetate, etc.; when the material to be prepared is a doped metal oxide, the cation source includes a metal salt that can provide the M metal element and a metal salt that can provide the A doping element, such as zinc acetate, magnesium acetate, etc.; the alkali source includes one or more of an organic base and an inorganic base, the organic base is selected from one or more of hexamethylenetetramine, tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, and urea, and the inorganic base is selected from one or more of sodium hydroxide, lithium hydroxide, potassium hydroxide, calcium hydroxide, ammonium hydroxide, sodium carbonate, and potassium carbonate; the solvent includes alcohols or dimethyl sulfoxide (DMSO). When preparing the electron transport material, the mobility of the electron transport layer 40 material can be precisely controlled by adjusting the type and content of the doping element, the amount of alkali source added, the post-treatment conditions and other parameters. In actual operation, the preparation can be made with reference to the method for regulating the mobility of the electron transport layer 40 material commonly used in the art. Taking the method of regulating the amount of alkali source added to control the electron mobility as an example, in some embodiments, the electron transport layer 40 material is ZnO. In order to adjust its electron mobility, tetramethylammonium hydroxide can be used as the alkali source. When preparing ZnO, the molar ratio of ZnO and tetramethylammonium hydroxide is controlled to be 1:1.5, and a mobility of 0.1×10 -3 cm 2 / Vs ZnO nanoparticles; the molar ratio of ZnO and tetramethylammonium hydroxide can also be controlled to 1:0.5, and a mobility of 5×10 -3 cm 2 / Vs of ZnO nanoparticles.
[0070] In some embodiments, the anode 10 is independently selected from a doped metal oxide particle electrode, a composite electrode of metal and metal oxide, a graphene electrode, a carbon nanotube electrode, a metal electrode or an alloy electrode. The material of the doped metal oxide particle electrode is selected from one or more of indium-doped tin oxide, fluorine-doped tin oxide, antimony-doped tin oxide, aluminum-doped zinc oxide, gallium-doped zinc oxide, indium-doped zinc oxide, magnesium-doped zinc oxide and aluminum-doped magnesium oxide. The composite electrode of metal and metal oxide is selected from AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS, ZnS / Al / ZnS. The material of the metal electrode is selected from one or more of Ag, Al, Cu, Mo, Au, Pt, Si, Ca, Mg and Ba.
[0071] In some embodiments, the cathode 30 is independently selected from a doped metal oxide particle electrode, a composite electrode of metal and metal oxide, a graphene electrode, a carbon nanotube electrode, a metal electrode or an alloy electrode. The material of the doped metal oxide particle electrode is selected from one or more of indium-doped tin oxide, fluorine-doped tin oxide, antimony-doped tin oxide, aluminum-doped zinc oxide, gallium-doped zinc oxide, indium-doped zinc oxide, magnesium-doped zinc oxide and aluminum-doped magnesium oxide. The composite electrode of metal and metal oxide is selected from AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS, ZnS / Al / ZnS. The material of the metal electrode is selected from one or more of Ag, Al, Cu, Mo, Au, Pt, Si, Ca, Mg and Ba.
[0072] In some embodiments, the light-emitting device 100 further includes a hole injection layer 60 disposed between the anode 10 and the hole transport layer 50, and the material of the hole injection layer 60 includes poly(ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS), poly[(9,9'-dioctylfluorenyl-2,7-diyl)-CO-(4,4'-(N-(p-butylphenyl))diphenylamine)] (TFB), polyarylamine, poly(N-vinylcarbazole), polyaniline, polypyrrole, N,N,N',N'-tetrakis(4-methoxyphenyl)-benzidine (TPD), 4-bis[N-(1-naphthyl)-N-phenyl-amino]biphenyl (α-NPD), 4,4',4"-tri[phenyl One or more of (m-tolyl)amino]triphenylamine (m-MTDATA), 4,4',4"-tri(carbazol-9-yl)triphenylamine (TCTA), 1,1-bis[(di-4-tolylamino)phenylcyclohexane (TAPC), 4,4',4"-tri(diphenylamino)triphenylamine (TDATA) doped with tetrafluoro-tetracyano-quinodimethane (F4-TCNQ), p-doped phthalocyanine (e.g., F4-TCNQ-doped zinc phthalocyanine (ZnPc)), F4-TCNQ-doped N,N'-diphenyl-N,N'-di(1-naphthyl)-1,1'-biphenyl-4,4"-diamine (α-NPD), and hexaazatriphenylene-capronitrile (HAT-CN).
[0073] In some embodiments, the thickness of the anode 10 is 20-200 nm; for example, it can be 20-40 nm, 30-60 nm, 50-80 nm, 55-90 nm, 70-100 nm, 90-120 nm, 110-140 nm, 130-150 nm, 140-170 nm, 160-200 nm, and the like.
[0074] In some embodiments, the thickness of the cathode 30 is 40-190 nm; for example, it can be 40-60 nm, 50-80 nm, 55-90 nm, 70-100 nm, 90-120 nm, 110-140 nm, 130-150 nm, 140-170 nm, 160-190 nm, and the like.
[0075] In some embodiments, the thickness of the hole transport layer 50 is 30 to 180 nm; for example, it can be 30 to 40 nm, 35 to 60 nm, 50 to 80 nm, 55 to 90 nm, 70 to 100 nm, 90 to 120 nm, 110 to 140 nm, 130 to 150 nm, 140 to 170 nm, 160 to 180 nm, and the like.
[0076] In some embodiments, the thickness of the electron transport layer 40 is 20-180 nm; for example, it can be 20-40 nm, 30-60 nm, 50-80 nm, 55-90 nm, 70-100 nm, 90-120 nm, 110-140 nm, 130-150 nm, 140-170 nm, 160-180 nm, and the like.
[0077] In some embodiments, the thickness of the hole injection layer 60 is 20-200 nm; for example, it can be 20-40 nm, 30-60 nm, 50-80 nm, 55-90 nm, 70-100 nm, 90-120 nm, 110-140 nm, 130-150 nm, 140-170 nm, 160-200 nm, and the like.
[0078] It is understandable that the light emitting device 100 may also be provided with some functional layers conventionally used in the light emitting device 100 to help improve the performance of the light emitting device 100, such as an electron blocking layer, a hole blocking layer, an interface modification layer, etc.
[0079] It can be understood that the light emitting device 100 can be an upright light emitting device or an inverted light emitting device.
[0080] Based on the above embodiments, the present application further proposes a method for preparing a light emitting device 100, which is used to prepare the above light emitting device 100. In some embodiments, the light emitting device 100 may be a positive light emitting device, and accordingly, the preparation method includes:
[0081] S10a, providing an anode 10;
[0082] S20a, sequentially disposing a hole functional layer, a light emitting layer 20 and an electron transport layer 40 on the anode 10;
[0083] S30 a , disposing the cathode 30 on the electron transport layer 40 .
[0084] In some other embodiments, the light emitting device 100 may be an inverted light emitting device, and accordingly, the preparation method includes:
[0085] S10b, providing a cathode 30;
[0086] S20b, sequentially disposing an electron transport layer 40, a light emitting layer 20 and a hole functional layer on the anode 10;
[0087] S30b, disposing the anode 10 on the electron transport layer 40 .
[0088] In steps S20a and S20b, the hole functional layer includes the hole transport layer 50 , or includes the hole transport layer 50 and the hole injection layer 60 . When the hole functional layer includes the hole transport layer 50 and the hole injection layer 60 , the hole injection layer 60 is disposed closer to the anode 10 .
[0089] In the preparation method of the light-emitting device 100, the preparation method of the anode 10, the light-emitting layer 20, the electron transport layer 40, the hole transport layer 50, the hole injection layer 60 and the cathode 30 can be achieved by conventional techniques in the art, such as chemical methods or physical methods. Among them, the chemical method includes chemical vapor deposition, continuous ion layer adsorption and reaction, anodization, electrolytic deposition, and coprecipitation. The physical method includes physical plating and solution method, among which the physical plating method includes: thermal evaporation coating, electron beam evaporation coating, magnetron sputtering, multi-arc ion plating, physical vapor deposition, atomic layer deposition, pulsed laser deposition, etc.; the solution method can be spin coating, printing, inkjet printing, blade coating, printing, dip pulling, immersion, spraying, roll coating, casting, slit coating, and strip coating.
[0090] The materials of the anode 10 , the light emitting layer 20 , the electron transport layer 40 , the hole transport layer 50 , the hole injection layer 60 and the cathode 30 are as described above and will not be described in detail here.
[0091] In some embodiments, after the light emitting device 100 is prepared, the step of packaging the light emitting device 100 is further included. The packaging process can be performed by a common machine packaging or by manual packaging. Preferably, in the environment of the packaging process, the oxygen content and the water content are both less than 0.1 ppm to ensure the stability of the light emitting device 100.
[0092] In addition, the present application also relates to a display device, which includes the light-emitting device 100. The display device can be any electronic product with a display function, including but not limited to smart phones, tablet computers, laptop computers, digital cameras, digital video cameras, smart wearable devices, smart weighing electronic scales, car displays, televisions or e-book readers, wherein the smart wearable device can be, for example, a smart bracelet, a smart watch, a virtual reality (VR) helmet, etc.
[0093] The technical scheme and technical effects of the present application are described in detail below through specific embodiments and comparative examples. The following embodiments are only some embodiments of the present application and do not specifically limit the present application.
[0094] Example 1
[0095] This example aims to investigate the effect of the number of quantum dot layers on device performance
[0096] Experimental Group 1
[0097] The structure of the QLED device in this experimental group is: anode, hole injection layer, hole transport layer, light-emitting layer, electron transport layer and cathode stacked from bottom to top. The thickness of each layer is: anode 120nm
[0098] , hole injection layer 90nm, hole transport layer 100nm, light emitting layer 20nm, electron transport layer 70nm, cathode 80nm.
[0099] (1) A glass substrate is provided, and ITO is evaporated on the glass substrate to form an anode.
[0100] (2) Spin coating a PEDOT:PSS material (a commercial product with a doping ratio of 1:6 and a solute content of 1.5 wt%) on the anode and heating at 150° C. for 15 min to obtain a hole injection layer.
[0101] (3) The substrate prepared in step (2) was transferred to a nitrogen atmosphere, and a hole transport material was spin-coated on the hole injection layer, and heated at 150° C. for 15 min to obtain a hole transport layer; wherein the hole transport material was TFB, and its HOMO energy level was −5.3 eV and its mobility was 3.0×10 -3 cm 2 / Vs.
[0102] (4) Spin coating an octane solution of quantum dot material on the hole transport layer, and heating at 80° C. for 10 min to obtain a light-emitting layer; wherein the quantum dot material includes red quantum dots CdSe / ZnSe / CdZnS, with a QY of 82%, an average particle size of 10 nm, a surface ligand of octanethiol, a mass content of octanethiol on the surface of the quantum dots of 10%, and a ratio of the thickness of the first shell layer ZnSe to the core radius of 1:1, and a ratio of the thickness of the second shell layer CdZnS to the core radius of 1:1; during spin coating, the spin coating speed is controlled to be 2000 rpm, the time is 30 s, and the concentration of the quantum dot material in the octane solution of the quantum dot material is 17 mg / ml, so as to control the light-emitting layer to be a double-layer film.
[0103] (5) Spin-coating an ethanol solution of an electron transport material with a concentration of 30 mg / ml on the light-emitting layer and heating at 100° C. for 8 min to obtain an electron transport layer; wherein the electron transport material is ZnO, and its electron mobility is 0.2×10 -3 cm 2 / Vs; the electron mobility is 0.2×10 -3 cm 2 / Vs ZnO preparation method is: weigh 1mmol Zn(Ac)2·2H2O and 10ml DMSO into a three-necked flask, and then stir at 25℃ until completely dissolved to obtain a first solution; dissolve 1.4mmol tetramethylammonium hydroxide in 10ml ethanol to obtain a second solution; then slowly add the second solution to the first solution; after the reaction is completed, add ethyl acetate to precipitate, centrifuge, and discard the supernatant; add anhydrous ethanol to dissolve, and then add ethyl acetate to precipitate and centrifuge. Repeat the above steps twice to obtain an electron mobility of 0.2×10 -3 cm 2 / Vs of ZnO nanoparticles.
[0104] (6) Placing the substrate obtained in step (5) in a vapor deposition chamber, vapor-depositing Ag on the electron transport layer to obtain a cathode, and encapsulating to obtain a QLED device.
[0105] Control group 1
[0106] The control group 1 scheme is basically the same as the experimental group 1, except that in the control group, the light-emitting layer is a single-layer film, and accordingly, in step (4), the average particle size of the quantum dot material is 20nm, and the QY is 40%; during spin coating, the spin coating speed is controlled to be 2000rpm, the time is 30s, and the concentration of the quantum dot material in the n-octane solution of the quantum dot material is 21mg / ml, so as to control the light-emitting layer to be a single-layer film. The other steps and parameters are the same as those of the experimental group 1.
[0107] Control group 2
[0108] The control group 2 scheme is basically the same as the experimental group 1, except that in this control group, the light-emitting layer is a four-layer film, and accordingly, in step (4), the average particle size of the quantum dot material is 5nm, and the QY is 75%; during spin coating, the spin coating speed is controlled to be 2000rpm, the time is 30s, and the concentration of the quantum dot material in the n-octane solution of the quantum dot material is 15mg / ml, so as to control the light-emitting layer to be a four-layer film. The other steps and parameters are the same as those of the experimental group 1.
[0109] (i) Take the semi-finished device obtained in step (4) during the preparation of experimental group 1, control group 1 and control group 2, wherein the top layer of the semi-finished device is the light-emitting layer. The roughness of the light-emitting layer is examined by AFM to evaluate its film-forming effect, and the results are recorded in Table 1.
[0110] (ii) Prepare the corresponding single carrier devices of experimental group 1, control group 1 and control group 2 respectively, and test the current density-voltage curve of the single carrier transport thin film device (HOD / EOD). Take the current density of the device at a constant voltage of 4V for comparison. Among them:
[0111] The preparation method of the single electron device (EOD) is basically the same as the preparation method of its corresponding complete QLED device, the only difference is that the hole injection layer and the hole transport layer are subtracted.
[0112] The preparation method of the single hole device (HOD) is basically the same as the preparation method of its corresponding complete QLED device, the only difference is that the electron transport layer is subtracted.
[0113] The results are recorded in Table 1.
[0114] (III) Take the devices made in experimental group 1, control group 1 and control group 2, and place the devices under 120°C for 15 minutes for heat treatment to accelerate the forward aging of the devices. Then, perform subsequent performance tests on the devices after the heat treatment, and record the results in Table 1. The detection method is as follows:
[0115] (1) The detection method of external quantum efficiency EQE is: the ratio of the number of electron-hole pairs injected into quantum dots to the number of emitted photons, the unit is %, which is an important parameter to measure the quality of electrophotoelectric devices and can be obtained by measuring with EQE optical testing instruments. The specific calculation formula is as follows:
[0116]
[0117] Among them, η e is the light output coupling efficiency, η γ is the ratio of the number of recombined carriers to the number of injected carriers, x is the ratio of the number of excitons that generate photons to the total number of excitons, K R is the radiation process rate, K NR is the rate of the non-radiative process.
[0118] Test conditions: carried out at room temperature, air humidity is 30-60%.
[0119] (2) The test method for life T95@1000nit is:
[0120] The time required for the device to reduce its brightness to a certain percentage of the maximum brightness when driven by a constant current or voltage. The time it takes for the brightness to drop to 95% of the maximum brightness is defined as T95, and this life is the measured life. In order to shorten the test cycle, the device life test is usually carried out at high brightness by accelerating device aging, and the life under high brightness is obtained by fitting the extended exponential decay brightness attenuation fitting formula. For example, the life under 1000nit is calculated as T95@1000nit. The specific calculation formula is as follows:
[0121]
[0122] Among them, T95 L For lifespan at low brightness, T95 His the measured lifetime under high brightness, L H To accelerate the device to the highest brightness, L L is 1000nit, A is the acceleration factor, and this experiment measured the lifespan of several groups of QLED devices at rated brightness and found that the A value was 1.7.
[0123] Table 1
[0124]
[0125] It can be seen from the above table:
[0126] The film quality of control group 1 is poor, which is manifested by the large leakage current of EOD device and HOD device, while both experimental group 1 and control group 2 have good roughness. At the same time, experimental group 1 has better EQE and T95@1000nit than control group 2, and its HOD device and EOD device have not only large current density at 4V, but also close current density. This shows that for the devices with the following collocation design: QY is greater than or equal to 70%, the first shell is ZnSe, and the second shell is CdZnS quantum dots, meet the "HOMO energy level is -5eV~-6eV, and the mobility is greater than 2.01×10 -3 cm 2 / Vs and less than 10×10 -3 cm 2 / Vs" and hole transport materials that meet the "mobility of 0.2×10 -3 ~0.5×10 -3 cm 2 / Vs" electron transport material; when other film conditions remain unchanged and other parameters of quantum dot materials remain unchanged, compared with single-layer or multi-layer films, the double-layer film light-emitting layer not only has better film quality, but also has more balanced carrier injection, showing a significantly longer service life. This shows that the double-layer film is more compatible with the above-mentioned matching design, which helps to significantly improve the life of the device while ensuring the luminous efficiency.
[0127] Example 2
[0128] This example aims to investigate the effect of the quantum dot shell structure on device performance.
[0129] The schemes of control groups 3 to 6 are basically the same as those of experimental group 1, with the only difference being that in each control group, the quantum dot material used in the light-emitting layer is changed to the material listed in Table 2 below.
[0130] Performance tests were performed on experimental group 1 and control groups 3 to 6, and the results are recorded in Table 2.
[0131] Table 2
[0132] Part Number Quantum dot core First Shell Second Shell QY(%) EQE(%) <![CDATA[T95 1000nit (hrs)]]> Experimental Group 1 CdSe ZnSe CdZ 82 18 3105 Control group 3 CdSe CdZ ZnS 90 16 870 Control group 4 CdSe CdZnSeS CdZ 80 14 694 Control group 5 CdSe ZnS CdZ 78 13 2182 Control group 6 CdSe ZnS ZnS 86 12 580
[0133] It can be seen from the above table that for devices with the same hole transport layer and electron transport layer design, when the shell structure of the light-emitting layer material is changed from ZnSe / CdZnS to other shell structures, the device life is greatly reduced. This shows that compared with other wide-bandgap shell materials, when the first shell is ZnSe and the second shell is CdZnS, holes can be better injected into the shell for effective recombination, which is manifested as higher EQE and longer device life.
[0134] Example 3
[0135] This example aims to investigate the effect of the size of the quantum dots QY on the device performance.
[0136] This embodiment also sets up experimental group 2, experimental group 3, and control group 7. Among them:
[0137] The experimental group or control group scheme is basically the same as experimental group 1, the only difference is that in each experimental group or control group, the quantum dot material used in the light-emitting layer is changed to the material with QY defined in the following Table 3. In specific implementation, QY can be changed by adjusting the thickness of the second shell layer.
[0138] Performance tests were performed on experimental groups 1 to 3 and control group 7, and the results are recorded in Table 3.
[0139] Table 3
[0140]
[0141] It can be seen from the above table that for devices with the same hole transport layer and electron transport layer design, when the light-emitting layer material is changed from a material with QY greater than or equal to 70% to a material with QY less than 70%, the device life and luminous efficiency are greatly reduced. This shows that compared with quantum dot materials with QY less than 70%, when materials with QY greater than or equal to 70% are selected, the device design optimization effect is better, which helps to improve the EQE and life of the device.
[0142] Example 4
[0143] This example aims to investigate the effect of the HOMO energy level of the hole transport material on the device performance.
[0144] This embodiment also sets up an experimental group 4 and a control group 8. Among them:
[0145] The experimental group scheme is basically the same as the experimental group 1, except that the hole transport material used in the hole transport layer in each experimental group is changed to the material in the following Table 4. The control group 8 scheme is basically the same as the experimental group 1, except that the hole transport layer is omitted in the control group 8.
[0146] Performance tests were performed on experimental groups 1 and 4 and control group 8, and the results are recorded in Table 4.
[0147] Table 4
[0148]
[0149]
[0150] It can be seen from the above table that compared with the control group 8, the experimental groups 1 and 4 have significantly higher EQE and lifetime, and among them, the effect of the experimental group 4 is the best. Obviously, when other device parameters remain unchanged, the use of hole transport materials with an energy level difference of 0.1 to 1.6 eV with the light-emitting layer is more conducive to improving hole injection, and the smaller the energy level difference between the light-emitting layer and the hole transport material, the higher the hole injection, which is manifested as better device performance.
[0151] Example 5
[0152] This example aims to investigate the effect of the mobility of the hole transport material on the device performance.
[0153] This embodiment also sets up experimental group 5 and control groups 9 to 12. Among them:
[0154] The experimental group or control group scheme is basically the same as that of experimental group 1, except that in each experimental group or control group, the hole transport material used in the hole transport layer is changed to the material in Table 5 below. Among them, the Chinese name of TCTA is 4,4',4"-tri(carbazole-9-yl)triphenylamine; CAS number is 139092-78-7. The Chinese name of TPD is N,N,N',N'-tetrakis(4-methoxyphenyl)-benzidine; CAS number is 122738-21-0. The Chinese name of CBP is 4,4'-bis(9H-carbazole-9-yl)biphenyl; CAS number is 58328-31-7. T5DP2,7 is derived from the literature "Constructing Effffective Hole Transport Channels in Cross-Linked Hole Transport Layer by Stacking Discotic Molecules for High Performance Deep Blue QLEDs".
[0155] Performance tests were performed on experimental groups 1 and 5 and control groups 9 to 12, and the results are recorded in Table 5.
[0156] Table 5
[0157]
[0158]
[0159] It can be seen from the above table:
[0160] Compared with the control group, the experimental group showed higher luminous efficiency and lifetime, indicating that compared with the four materials provided by the control group, the materials provided by the experimental group are more compatible with the device provided in this embodiment. Obviously, for the use of quantum dots with QY greater than or equal to 70% and shell layer of ZnSe / CdZnS to prepare the double-layer film luminescent layer, and the use of materials with electron mobility of 0.2×10 -3 ~0.5×10 -3 cm 2 / Vs for the device with electron transport layer, the hole mobility of the hole transport material used is greater than 2.01×10 -3 cm 2 / Vs and less than 10×10 -3 cm 2 / Vs, the carrier balance in the device is better, which helps to significantly improve the efficiency of the device.
[0161] Example 6
[0162] This example aims to investigate the effect of the mobility of the electron transport material on the device performance.
[0163] This embodiment also sets up control groups 13 to 16. Among them:
[0164] The control group scheme is basically the same as the experimental group 1, the only difference is that in each control group, the electron transport material used in the electron transport layer is changed to the material in the following Table 6.
[0165] The mobility is 5×10 -3 The preparation method of ZnO is as follows: weigh 1mmol of Zn(Ac)2·2H2O and 10ml of DMSO into a three-necked flask, and then stir at 25°C until completely dissolved to obtain a first solution; dissolve 0.5mmol of tetramethylammonium hydroxide in 10ml of ethanol to obtain a second solution; then slowly drop the second solution into the first solution; after the reaction is completed, add ethyl acetate to precipitate, centrifuge, and discard the supernatant; add anhydrous ethanol to dissolve, and then add ethyl acetate to precipitate and centrifuge. Repeat the above steps twice to obtain an electron mobility of 5×10 -3 cm 2 / Vs of ZnO nanoparticles.
[0166] The mobility is 0.1×10 -3 The preparation method of ZnO is as follows: compared with the mobility of 5×10 -3The only difference is that the molar ratio of Zn(Ac)2·2H2O to tetramethylammonium hydroxide is 1:1.5; the other parameters and steps are the same.
[0167] The electron mobility is 0.8×10 -3 cm 2 / Vs electron transport layer preparation method is: weigh 0.85mmol Zn(Ac)2·2H2O, 0.15mmol Mg(Ac)2·4H2O and 10ml DMSO into a three-necked flask, and then stir at 25℃ until completely dissolved to obtain a first solution; dissolve 1.5mmol tetramethylammonium hydroxide in 10ml ethanol to obtain a second solution; then slowly add the second solution to the first solution; after the reaction is completed, add ethyl acetate to precipitate, centrifuge, and discard the supernatant; add anhydrous ethanol to dissolve, and then add ethyl acetate to precipitate and centrifuge. Repeat the above steps twice to obtain ZnMgO nanoparticles. The ZnMgO nanoparticles are dispersed in ethanol, spin-coated on the light-emitting layer to form a solid film, and then placed in an oxygen atmosphere and UV for 5min at 365nm and 1200W power to obtain an electron mobility of 0.8×10 -3 cm 2 / Vs ZnMgO electron transport layer.
[0168] The mobility is 0.01×10 -3 The preparation method of ZnMgO is as follows: weigh 0.9mmol Zn(Ac)2·2H2O, 0.1mmol Mg(Ac)2·4H2O and 10ml DMSO into a three-necked flask, and then stir at 25°C until completely dissolved to obtain a first solution; dissolve 1.5mmol tetramethylammonium hydroxide in 10ml ethanol to obtain a second solution; then slowly add the second solution to the first solution; after the reaction is completed, add ethyl acetate to precipitate, centrifuge, and discard the supernatant; add anhydrous ethanol to dissolve, and then add ethyl acetate to precipitate and centrifuge. Repeat the above steps twice to obtain a mobility of 0.01×10 -3 ZnMgO nanoparticles.
[0169] Performance tests were performed on experimental group 1 and control groups 13-16, and the results are recorded in Table 6.
[0170] Table 6
[0171]
[0172]
[0173] It can be seen from the above table:
[0174] Compared with the control group, the experimental group showed higher luminous efficiency and lifetime, indicating that compared with the four materials provided by the control group, the electron transport material provided by the experimental group is more compatible with the device provided in this embodiment. Obviously, for the preparation of the double-layer film luminescent layer using quantum dots with QY greater than or equal to 70% and a shell layer of ZnSe / CdZnS, and the use of materials with a hole mobility greater than 2.01×10 -3 cm 2 / Vs and less than 10×10 -3 cm 2 / Vs hole transport material to prepare the hole transport layer of the device, the electron transport material used is an electron mobility of 0.2×10 -3 ~0.5×10 -3 cm 2 / Vs, the carrier balance in the device is better, which helps to significantly improve the efficiency of the device.
[0175] The light-emitting device and display device provided in the embodiments of the present application are introduced in detail above. Specific examples are used in this article to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method of the present application and its core idea. At the same time, for technical personnel in this field, according to the idea of the present application, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.
Claims
1. A light emitting device, characterized in that: The invention comprises an anode, a hole transport layer, a light-emitting layer and a cathode which are stacked in sequence, wherein the material of the light-emitting layer comprises quantum dots, and the thickness of the light-emitting layer is 1.6 to 2.3 times the average particle size of the quantum dots; The mobility of the hole transport layer material is greater than 2.01×10 -3 cm 2 / Vs, less than 10×10 -3 cm 2 / Vs.
2. The light emitting device according to claim 1, characterized in that: The energy level difference between the hole transport layer and the light emitting layer is 0.1 to 1.6 eV; and / or, The mobility of the material of the hole transport layer is 2.5×10 -3 ~5×10 -3 cm 2 / Vs.
3. The light emitting device according to claim 2, characterized in that: The HOMO energy level of the material of the hole transport layer is -5 eV to -6 eV.
4. The light emitting device according to any one of claims 1 to 3, characterized in that: The material of the hole transport layer includes any one of TFB and V-TPAVCBP:10%OPPI.
5. The light emitting device according to claim 1, characterized in that: The fluorescence quantum yield of the quantum dots is greater than or equal to 70%; and / or, The average particle size of the quantum dots is greater than 8 and less than 11 nm; and / or, The quantum dot is a core-shell structure quantum dot, and the quantum dot has a first shell layer and a second shell layer from the inside to the outside, the material of the first shell layer is ZnSe, and the material of the second shell layer is CdZnS.
6. The light emitting device according to claim 5, characterized in that: The ratio of the thickness of the first shell layer to the radius of the core of the quantum dot is 0.5 to 2:1; and / or, The ratio of the thickness of the second shell layer to the radius of the core of the quantum dot is 0.4 to 2:1; and / or, the core material is selected from at least one of II-VI compounds, IV-VI compounds, III-V compounds and I-III-VI compounds; the II-VI compounds are selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, Cd At least one of ZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe; the IV-VI group compound is selected from SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, At least one of PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, SnPbSTe; the III-V compound is selected from GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InN P, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb; the I-III-VI group compound is selected from at least one of CuInS2, CuInSe2 and AgInS2.
7. The light emitting device according to claim 1, characterized in that: The light emitting device further comprises an electron transport layer disposed between the cathode and the light emitting layer; The mobility of the material of the electron transport layer is 0.2×10 -3 ~0.5×10 -3 cm 2 / Vs; And / or, the average particle size of the material of the electron transport layer is 2 to 12 nm.
8. The light emitting device according to claim 1, characterized in that: The light-emitting device also includes an electron transport layer arranged between the cathode and the light-emitting layer, and the material of the electron transport layer includes one or more of metal oxides and doped metal oxides; the metal oxide includes one or more of ZnO, TiO2, SnO2, ZrO, Al2O3, WO3, HfO3, Ta2O3, ZrSiO4, BaTiO3, and BaZrO3; the metal oxide in the doped metal oxide includes multiple of ZnO, TiO2, SnO2, ZrO, Al2O3, WO3, HfO3, Ta2O3, ZrSiO4, BaTiO3, and BaZrO3, and the doping element includes one or more of Al, Mg, Li, In, Ga, Cd, Cs, and Cu; And / or, the anode and the cathode are independently selected from a doped metal oxide particle electrode, a composite electrode of a metal and a metal oxide, a graphene electrode, a carbon nanotube electrode, a metal electrode or an alloy electrode, the material of the doped metal oxide particle electrode is selected from one or more of indium-doped tin oxide, fluorine-doped tin oxide, antimony-doped tin oxide, aluminum-doped zinc oxide, gallium-doped zinc oxide, indium-doped zinc oxide, magnesium-doped zinc oxide and aluminum-doped magnesium oxide, the composite electrode of the metal and the metal oxide is selected from AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS, ZnS / Al / ZnS, and the material of the metal electrode is selected from one or more of Ag, Al, Cu, Mo, Au, Pt, Si, Ca, Mg and Ba; And / or, the light-emitting device further comprises a hole injection layer disposed between the anode and the hole transport layer, wherein the material of the hole injection layer comprises poly(ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS), poly[(9,9'-dioctylfluorenyl-2,7-diyl)-CO-(4,4'-(N-(p-butylphenyl))diphenylamine)], polyarylamine, poly(N-vinylcarbazole), polyaniline, polypyrrole, N,N,N',N'-tetrakis(4-methoxyphenyl)-benzidine, 4-bis[N-(1-naphthyl)- One or more of N-phenyl-amino]biphenyl, 4,4',4"-tri[phenyl(m-tolyl)amino]triphenylamine, 4,4',4"-tri(carbazole-9-yl)triphenylamine, 1,1-bis[(di-4-tolylamino)phenylcyclohexane, 4,4',4"-tri(diphenylamino)triphenylamine doped with tetrafluoro-tetracyano-quinodimethane, p-doped phthalocyanine, F4-TCNQ doped N,N'-diphenyl-N,N'-di(1-naphthyl)-1,1'-biphenyl-4,4"-diamine, and hexaazatriphenylene-capronitrile.
9. The light emitting device according to claim 8, characterized in that: The thickness of the anode is 20 to 200 nm; and / or, The thickness of the cathode is 40 to 190 nm; and / or, The thickness of the hole transport layer is 30 to 180 nm; and / or, The thickness of the electron transport layer is 20 to 180 nm; and / or, The hole injection layer has a thickness of 20 to 200 nm.
10. A display device, characterized in that: The display device comprises the light emitting device according to any one of claims 1 to 9.
